Edukasi Metode CERDIK Dan PATUH Modifikasi Gaya Hidup Sehat Dalam Upaya Mencegah Kejadian Stroke Berulang - Ni Luh Putu Thrisna Dewi; Ni Made Nopita Wati; Desak Made Ari Dwi Jayanti; Ni Kadek Yuni Lestari; I Nyoman Sudarma (Poltekkes Kemenkes Surakarta, 2022)
Background: The prognosis of stroke after an attack is very diverse. Some can recover, as usual, and some live with residual symptoms such as mild to severe disability. However, a stroke for the first time has a significant risk of a repeat attack. So it is necessary to make lifestyle modifications to the risk factors they have, one of which is through the community movement (GERMAS) in the form of education about the CERDIK and PATUH Healthy Lifestyle, which synergizes with this PKM, which is to increase the understanding of families and post-stroke sufferers so that they behave to improve their lifestyle so that it can prevent recurrent strokes. Methods: This community service is carried out to anticipate recurrent stroke events, which involves the community service team from Stikes Wika and people with stroke who still need to understand managing risk factors for recurrent attacks. Community service is conducted offline through counseling with activity partners under the auspices of the Amaranne Foundation. (Tapasya Stroke Center) Tabanan Bali. Results: Of community service activities, people with stroke can change their behavior for the better after knowing how to prevent repeated attacks, with a post-test score of 72% on good points. Conclusion: This illustrates that understanding stroke survivors and their families will stimulate a healthy lifestyle without repeated attacks.